Review of SQL Injection : Problems and Prevention - Mohd Amin Mohd Yunus; Muhammad Zainulariff Brohan; Nazri Mohd Nawi; Ely Salwana Mat Surin; Nurhakimah Azwani Md Najib; Chan Wei Liang (JOIV : International Journal on Informatics Visualization, 2018)
SQL injection happened in electronic records in database and it is still exist even after two decades since it first happened. Most of the web-based applications are still vulnerable to the SQL injection attacks. Although technology had improved a lot during these past years, but, hackers still can find holes to perform the SQL injection. There are many methods for this SQL injection to be performed by the hackers and there is also plenty of prevention for the SQL injection to be happened. The vulnerability to SQL injection is very big and this is definitely a huge threat to the web based application as the hackers can easily hacked their system and obtains any data and information that they wanted anytime and anywhere. This paper can conclude that several proposed techniques from existing journal papers used for preventing SQL injection. Then, it comes out with Blockchain concept to prevent SQL injection attacks on database management system (DBMS) via IP.